(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
The study was performed to determine the diversity and distribution of Hymenoptera across the environmental gradient ranging from fringe forest, mid forest to inner forest. The study was conducted in a selected area of Tuba Island Forest Reserve from 17th to 21st September 2020 using Malaise trap, an insect capturing trap. During this study, a total of 133 individuals of Hymenoptera were sampled from 12 families and 27 morphospecies. Hymenoptera was most abundantly found in the forest fringe with 64 individuals (11 families, 25 morphospecies) and least abundant in the inner forest with 26 individuals (7 families, 8 morphospecies). The top three highest number of individuals recorded were Formicidae (43 individuals), Braconidae (28 individuals) and Ichneumonidae with 27 individuals. Shannon-Weiner Diversity Index (H’) showed that the forest fringe had the highest diversity value with H’=1.80 while the lowest was recorded in the mid forest with H’=1.43. The Evenness Index (E’) was highest at mid forest (E’=0.81) and the Margalef Richness Index (R’) value recorded the highest at forest fringe indicating a high species richness with R’=2.40. Kruskal-Wallis test reveals that the distribution of Hymenopterans from the forest fringe to the inner forest did not differ significantly with P>0.05. High similarities in microclimate variables (monsoon season, temperature, humidity, and light intensity), resources availability, forest features, hiding places, and the presence of predators are among the factors influencing the homogeneity of the composition and abundance of Hymenoptera in Tuba Island. This study is the first checklist of Hymenoptera in Tuba Island and can be utilised as a baseline dataset for further ecological research at Tuba Island.